Compton scattering of polarized electron beam - Drebot, I.; Karnaukhov, I.; Zelinsky, A. (Вопросы атомной науки и техники, 2004)
Compton scattering of polarized photon beam by polarized relativistic electron beam is considered in the report. The numerical comparison of Compton scattering intensity and polarization intensity has been carried out for different directions of initial photon and electron polarization. It was shown that the use of polarized beam leads to considerable increasing of Compton scattering intensity in the range of high photon energy for initial electron beam energy beginning from 5 GeV. The effect of initial polarization of photon and electron beams to final polarization of scattered photon beam was considered.